2014
DOI: 10.1074/jbc.m113.511030
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Cellular, and Biophysical Characterization of a Potent Inhibitor of Mutant Isocitrate Dehydrogenase IDH1

Abstract: Background: IDH1 R132H, implicated in glioblastoma and AML, produces the oncometabolite 2-HG. Results: A detailed binding mechanism of a small molecule inhibitor (ML309) is proposed. Conclusion: ML309 competes with ␣-KG but is uncompetitive with NADPH and rapidly and reversibly affects cellular 2-HG levels. Significance: Understanding IDH1 R132H inhibition sets the stage for targeting IDH1 R132H for the treatment of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 22 publications
(42 reference statements)
3
106
0
Order By: Relevance
“…Inhibitors of IDH1 MT and IDH2 MT were recently developed (23)(24)(25)(26)(27). Clinical trials of the IDH1 R132H inhibitor AGI-5198 (ClinicalTrials.gov NCT02073994) are in progress in solid tumors.…”
Section: Idh1mentioning
confidence: 99%
“…Inhibitors of IDH1 MT and IDH2 MT were recently developed (23)(24)(25)(26)(27). Clinical trials of the IDH1 R132H inhibitor AGI-5198 (ClinicalTrials.gov NCT02073994) are in progress in solid tumors.…”
Section: Idh1mentioning
confidence: 99%
“…This lead was demonstrated to affect growth and promote differentiation in mutant IDH1 glioma cells, confirming the target relevance (Rohle et al, 2013). A similar medicinal chemistry and assay approach was used by the National Center for Advancing Translational Sciences and Agios to generate the phenyl-glycine analog ML309 (Davis et al, 2014). The Agios efforts have progressed to yield mutant IDH1 (AG-120) (2015), mutant IDH2 (AG-221) (Stein, 2015), and pan-mutant IDH1/2 (AG-881, brainpermeable) inhibitors.…”
Section: A Case Study 1: Mutant Isocitrate Dehydrogenases 1 Andmentioning
confidence: 99%
“…This inhibitor binds competitively to mutant IDH1 and acts as a reversible inhibitor in competition with α-KG, and not in competition with NADPH. 99 The compound inhibits 2-HG production in glioma cells, with an IC 50 =250 nM, and had displayed minimal in vivo toxicity. 99 A number of studies have investigated the structural and mechanistic aspects of IDH inhibition by the various IDH inhibitors.…”
Section: Idh Inhibitorsmentioning
confidence: 99%
“…99 The compound inhibits 2-HG production in glioma cells, with an IC 50 =250 nM, and had displayed minimal in vivo toxicity. 99 A number of studies have investigated the structural and mechanistic aspects of IDH inhibition by the various IDH inhibitors. Kinetic and structural studies have suggested that the inhibitors could be divided into two categories: (a) those able to bind to the α-KG/ isocitrate site and then act as binding competitors; (b) those able to bind allosterically to the interface between the two promoters of the IDH enzyme molecule dimer.…”
Section: Idh Inhibitorsmentioning
confidence: 99%